2003
DOI: 10.1046/j.1472-765x.2003.01324.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of W-7, a calmodulin antagonist on phospholipid biosynthesis inCandida albicans

Abstract: Aim: This study was undertaken to investigate the role of calmodulin in phospholipid biosynthesis in Candida albicans using W-7, a calmodulin antagonist. Methods: Cells were grown as shake cultures in the absence and presence of W-7 at different concentrations. Changes in cell mass, phospholipid content and incorporation of labelled precursor into phospholipid and activities of respective enzymes have been studied. Results: Decreased incorporation of labelled acetate into total lipids and phospholipids was obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…4A). To delineate relation between CaMKI activation and cell cycle progression, MA104 cells were either infected with RV SA11 strain at 3 moi or kept mock infected in presence or absence of either calcium chelator BAPTA-AM which chelates Ca þ 2 ions and inhibits CaM activation or CaM inhibitor W7 which bind selectively to CaM and inhibit its downstream functions (Dhillon et al, 2003), for indicated time points followed by cell cycle analysis using flowcytometry (treatments were done post viral absorption). Quantitive analysis revealed that both BAPTA-AM and W7 inhibit cell cycle progression from G1 to S phase as found in only SA11 infected MA104 cells (Fig.…”
Section: Rv Infection Drives G 1 To S Phase Transition In a Ca þ 2 /Cmentioning
confidence: 99%
“…4A). To delineate relation between CaMKI activation and cell cycle progression, MA104 cells were either infected with RV SA11 strain at 3 moi or kept mock infected in presence or absence of either calcium chelator BAPTA-AM which chelates Ca þ 2 ions and inhibits CaM activation or CaM inhibitor W7 which bind selectively to CaM and inhibit its downstream functions (Dhillon et al, 2003), for indicated time points followed by cell cycle analysis using flowcytometry (treatments were done post viral absorption). Quantitive analysis revealed that both BAPTA-AM and W7 inhibit cell cycle progression from G1 to S phase as found in only SA11 infected MA104 cells (Fig.…”
Section: Rv Infection Drives G 1 To S Phase Transition In a Ca þ 2 /Cmentioning
confidence: 99%
“…9D). This effect may be due to antagonistic activity of the W-7 against the Ca 2+ -CaM complex [36] which is required for efficient viral replication & assembly.…”
Section: Resultsmentioning
confidence: 99%
“…Cytotoxicity of Fura2-AM was tested using MTT assay (data not shown) [36]. HT-29 cells were treated with increasing concentration (0–50 µM) of W-7 (in DMSO), a CaM antagonist and after 12 h, cell viability was measured (data not shown).…”
Section: Methodsmentioning
confidence: 99%